PARTIAL MELTING IN THE UPPER MANTLE OF THE BAIKAL RIFT, AS INFERRED FROM THE STUDY OF GLASSES IN LHERZOLITE NODULES AND MEGACRYSTS - Murav'yeva N.S.; Senin V.G.; Polyakov A.I. (My University, 1988)
Analysis of glasses in lherzolite nodules should allow the process of partial melting to be traced in its earliest stage, because such rocks are among the few sources of information on the chemical and mineral compositions of the upper mantle. Mantle xenoliths in alkalic basalts of the Baikal rift zone consist of spinel lherzolite, garnet-spinel lherzolite and pyroxenite of different composition. Study of glasses in the spinel lherzolite nodule leads to the conclusion that the primary melts generated within the upper mantle of the Baikal rift were equivalent in composition to andesite and andesite-basalt. However, the degree of melting during their generation was so low that they could not have separated from the matrix and been transported to the surface together with the host inclusions. Glass compositions and microtextures in the Tokinskiy Stanovik lherzolite nodules indicate that water-bearing fluids rich in alkalies, especially sodium, participated in melting of the upper mantle. The composition of such mantle fluids evidently varied with depth.